Monitoring of obstetric pathology of cows in agricultural enterprises of Rivne region - R. M. Sachuk; Ya. S. Stravsky; O. A. Katsaraba; S. V. Zhigalyuk; O. V. Kulinich; M. I. Kushnir (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2019)
In recent years, there has been a problem of low reproductive capacity of cows in the farms of Rivne region. A retrospective analysis conducted by us in the region showed that 57.0% of dairy farms in the region have to be re-inseminated over several sexual cycles. In this case, 53.0% of cows are fertilized after 150–180 days after calving and give 3500–4000 kg of milk per year. The enterprises have a prolonged service period, which is 130–140 days. There is a shortage of calves, namely their output per 100 cows is 65,0–70,0. In addition, farms keep a large number of cows with poor feed conversion efficiency. An example is the situation in the farms of LLC SGP “them. Volovikova” of Goschansky District, FG “Mriya”, SE “Belokrynitske” of Rivne District, PSP “Ukraine” of Dubrovytskyi District, where 8765 cows that were bred from November to February 2016-18 were subjected to obstetric dispensation, namely: the service period was 148–154 days, and the yield of calves per 100 cows was 70.0–76.0. At the diagnostic stage of obstetric examination, the spread of obstetric pathology in cows during periods of dryness, calving and post-calving was analyzed. In the period of dryness, there were cases of subsidence to childbirth 5.2% (1.7–17.0%), udder edema 4.6% (2.4–13.8%, and subclinical mastitis 6.8%. Metabolic disorders include diseases such as ketosis 3.5% (0.8–12.0%) and fatty liver syndrome 5.7% (5.0–7.0) In the cows of FG “Mriya” the level of ketone bodies was at the level of 2.0 ± 0.04 mmol/l. In the course of the farm surveys, the pathological course of childbirth was recorded in 1431 cases, representing 16.3% of the total number of surveyed and 25.9% of feral animals. In addition, 534 cows (6.1%) experienced mechanical damage and trauma to the vulva and vagina mucosa. 426 cows (4.9%) noted further development of postpartum vulvо-vaginitis and erosion of the genital organs. In 1777 cows (20.2%) cases of postpartum paresis were recorded, of which the largest share was 27.8% in FG “Mriya”. In the cows of the farms studied, the most common form of mastitis was subclinical, which was found in 3.1% – 42.0% of cows. The clinical form accounted for 38.0% of diagnoses. In FG “Mriya” of the Rivne region, the subclinical form of mastitis was recorded most in cows post-otelny period – up to 40.0%, whereas in dry period – 11.0% of cases. PSP “Ukraine” practically did not diagnose the clinical form of mastitis. Prospective in the study of the etiology of metabolic and obstetric diseases will be the study of individual indicators of quality and safety of feed, clinical and laboratory studies of pathology of the reproductive system, which will become the basis for early diagnosis of these diseases.